A Mixture of Chicken Viscera, Housefly Larvae and Spirulina Waste as Replacement of Fishmeal in Nile Tilapia (Oreochromis niloticus) Diets - ALOFA, Cayen Sédro; ABOU, YOUSSOUF (My University, 2021)
This research investigated different blends of spirulina waste (SW), chicken viscera meal (CVM) and housefly maggot meal (HMM) as alternative protein sources on growth performance, feed utilization and body composition of Oreochromis niloticus fingerlings. Triplicate groups of male fish (initial mean weight, 6.09±0.5g) were fed a commercial feed Skretting (SK), fish meal (FM) based-diet D0 (30%FM), diet D1 (FM+SW+HMM), diet D2 (FM+SW+CVM), diet D3 (FM+HMM+CVM) and diet D4 (SW+HMM+CVM) for 84 days. Diets were isonitrogenous (35% crude protein) and isoenergetic (19 KJ/g gross energy). No effects were found on survival rate and body protein content of fish fed experimental diets. Specific growth rate, weight gain, feed conversion ratio and protein efficiency ratio (PER) of fish fed D0 and SK did not differ significantly from those fed diet D3. These parameters were significantly lower in fish fed the other diets (P<0.05). Feed intake significantly decreased in fish fed diet D1 and D2 while PER obtained did not differ than those fed control diets. The higher profit index was recorded in the tested diets and the lower in the control diets. The results of this study indicate that fishmeal level for O. niloticus could be reduced to 5 % by inclusion of CVM and HMM in combination.
Keywords: Nile tilapia; Combination; Unconventional protein sources; Growth; Profitability